How Do Migration and Remittances Affect Inequality? : A Case Study of Mexico - Koczan, Zsoka (IMF Working Papers; Working Paper ;, 2018)
The poverty-reducing effects of remittances have been well-documented, however, their effects on inequality are less clear. This paper examines the impact of remittances on inequality in Mexico using household-level information on the receiving side. It hopes to speak to their insurance role by examining how remittances are affected by domestic and external crises: the 1994 Mexican Peso crisis and the Global Financial Crisis. We find that remittances lower inequality, and that they become more pro-poor over time as migration opportunities become more widespread. This also strengthens their insurance effects, mitigating some of the negative impact of shocks on the poorest.